Evaluating the Co-relationship between Patient Mindfulness and Dental Treatment Satisfaction: A Cross-sectional Study - Seema Sathe; Khushbu Nimish Doshi; Anjali Bhoyar; Tanvi Jaiswal; Mithilesh M Dhamande; Rajanikanth Kambala; Ashika Singhania (Journal of Clinical and Diagnostic Research)
Introduction: There is a longstanding belief that the quality of mindfulness contributes to a person’s enhanced well-being. The concept of mindfulness has gained increasing attention in healthcare settings, including dentistry, as a potential factor influencing patient experiences and outcomes. The present study aimed to explore how mindfulness influences dental treatment satisfaction, as psychological factors such as anxiety significantly impact patient experiences. Understanding this correlation could lead to better strategies for reducing dental anxiety, improving patient satisfaction and enhancing overall treatment outcomes in dental care. Aim: To evaluate the correlation between patient mindfulness and dental treatment satisfaction. Materials and Methods: This research was a cross-sectional, questionnaire-based study with a sample size of 303 patients selected from the Outpatient Department (OPD) of the Department of Prosthodontics and Crown and Bridge at Sharad Pawar Dental College and Hospital, Wardha, Maharashtra, India, from June 2023 to November 2023. A questionnaire was used to assess patient mindfulness as well as their satisfaction with various aspects of treatment. The Mindful Attention Awareness Scale (MAAS) questionnaire was distributed and completed by the patients prior to treatment and a single evaluator assessed the responses without knowing the treatment status of the patients. The patients then underwent the treatment for which they had visited the hospital. Upon completion of the treatment, the Patient Satisfaction Questionnaire (PSQ) was distributed and filled out by the patients. This was assessed using the Likert scale. A correlative evaluation was then conducted after assessing the individual scores on the questionnaires using Pearson’s Correlation Coefficient. Results: Using Pearson’s correlation coefficient, a positive correlation was found between the scores of the MAAS and the PSQ (r=0.347, p<0.01). This indicates that as the MAAS score of the patient increases, the PSQ score also increases. Conclusion: The evaluation of the correlation between patient mindfulness and dental treatment satisfaction indicates that higher levels of mindfulness are associated with increased satisfaction during dental procedures. This relationship suggests that mindfulness may enhance patients’ overall experiences.